The Codification of Syar'i Norms in The Compilation of Sharia Economic Law - Burhanuddin Susamto; Thohir Luth; Masruchin Rubai; Jazim Hamidi (Universitas Muhammadiyah Sidoarjo, 2017)
It is a fact that The Compilation of Sharia Economic Law (CSEL) was arrangedfor a guiding of sharia principle in the settlement of Islamic economic disputes. As a guiding of sharia principle, ideally CSEL norms should contain the values of sharia as desired by God.The purpose of this article is to ascertain the level validity of CSEL norms when viewed from a sharia perspective. To achieve the intended purpose, the author used normative legal research and use the approach of theory fiqhmu’âmalâh iqtishâdiyah and fatwâ of DSN-MUI. From the analysis we know that CSEL norms has not legitimized the Islamic sharia as a fundamental principle formally, so consequently the existence of the norm seems to replace God's verses. Of the total norms in CSEL, there are 98.48% norms which has contained the shar'î values, while approximately 1.52% is still found problematic normsso they needs to be revised.